Wind Loads for Stability Design of Large Multi-Span Duo-Pitch Greenhouses - Bronkhorst, A. J.; Geurts, C. P. W.; van Bentum, C. A.; van der Knaap, L. P. M.; Pertermann, I. (Frontiers in Built Environment, 2017)
An atmospheric boundary layer wind tunnel study was performed to determine the overall horizontal wind load on multi-span duo-pitch greenhouses. The results of this study are intended for the stability design of inflexible cladding system greenhouses (designated as Class A in EN 13031-1) with roof pitch angles of 23° to 24° and ridge heights of 7.5 m to 8 m. Both static force and fluctuating pressure measurements were performed to determine the overall horizontal wind force. The results obtained with the static force measurements show that the overall horizontal wind force increases linearly with increasing number of spans. The overall horizontal wind load determined with the mean pressure coefficients derived from the fluctuating pressure measurements was found to be in good agreement with the static force measurements. An investigation into the correlation of the roof pressures showed that these pressures are relatively little correlated, especially if the pressures on multiple spans are considered. The overall horizontal force on the roof of multi-span buildings reduces significantly because of this lack of correlation. Accounting for the lack of correlation between the roof pressures on a 30-span model resulted in a 65% reduction of the peak horizontal wind force on the roof. Finally, the magnitude of the mean and maximum peak pressure coefficients determined in this study show there is a need for specification of positive values in EN 1991-1-4 and EN 13031-1 for the pressure coefficients on wind-facing roof faces beyond the first roof span. A comparison was made of the overall horizontal wind forces determined in the current study and calculated with European codes for wind load assessment on greenhouses. EN 13031-1 provides non-conservative outcomes for the overall horizontal wind force on the investigated duo-pitch greenhouse type with more than 30 spans. On the other hand, EN 1991-1-4 is increasingly conservative with larger number of spans.